A deep tissue fluorescence imaging system with enhanced SHG detection capabilities. Issue 5 (7th March 2014) - Crosignani, Viera; Jahid, Sohail; Dvornikov, Alexander S.; Gratton, Enrico
ABSTRACT We describe a novel two‐photon fluorescence microscopy system capable of producing high‐quality second harmonic generation (SHG) images in thick turbid media by using an innovative detection system. This novel detection system is capable of detecting photons from a very large surface area. This system has proven effective in providing images of thick turbid samples, both biological and artificial. Due to its transmission detection geometry, the system is particularly suitable for detecting SHG signals, which are generally forward directed. In this article, we present comparative data acquired simultaneously on the same sample with the forward and epidetection schemes. Microsc. Res. Tech. 77:368–373, 2014. © 2014 Wiley Periodicals, Inc.